2021
DOI: 10.1088/1755-1315/715/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glutamine synthetase activity from Lactobacillus hilgardii LMG 7934

Abstract: Lactic acid bacteria (LAB) are Gram-positive, non-spore forming, facultative anaerobic or microaerophilic bacteria living in various nutrients-rich ecological niches and are widely used for dairy food and silage production as well as probiotics for the Human and animals. While bacteria can assimilate various nitrogen-containing compounds, the glutamine and ammonium are the most preferred nitrogen sources since they could be directly involved into the nitrogen metabolism of the cell. In bacterial cells, the glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This shows that LAB (L. paracasei Lpc-37) was the key contributor to the utilization of glutamine (via glutaminase), which has been shown to be the preferred source of nitrogen by LAB . The majority of other amino acids were not utilized by LAB due to the lack of both isocitrate dehydrogenase and nicotinamide adenine dinucleotide-dependent glutamate dehydrogenase (NAD–GDH) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that LAB (L. paracasei Lpc-37) was the key contributor to the utilization of glutamine (via glutaminase), which has been shown to be the preferred source of nitrogen by LAB . The majority of other amino acids were not utilized by LAB due to the lack of both isocitrate dehydrogenase and nicotinamide adenine dinucleotide-dependent glutamate dehydrogenase (NAD–GDH) .…”
Section: Resultsmentioning
confidence: 99%
“…This shows that LAB (L. paracasei Lpc-37) was the key contributor to the utilization of glutamine (via glutaminase), which has been shown to be the preferred source of nitrogen by LAB. 38 The majority of other amino acids were not utilized by LAB due to the lack of both isocitrate dehydrogenase and nicotinamide adenine dinucleotide-dependent glutamate dehydrogenase (NAD−GDH). 39 Several studies have demonstrated different pathways for the increase in the glutamate content during LAB metabolism, including the action of glutamate synthase (GS−GOGAT) or glutaminase, 40,41 production from glucose via Krebs cycle intermediates in LAB, 42 and elevated NADP-GDH and glutamic acid exporter gene activity, resulting in the conversion of α-ketoglutarate to glutamate along with the excretion of glutamate into beer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%